EFEK INTERVENSI BUAH TAKOKAK (Solanum torvum Swartz) TERHADAP KADAR SUPEROKSIDA DISMUTASE ERITROSIT DAN 8-ISOPROSTAN SERUM PADA WANITA DEWASA GEMUK - Novitasari, Putri; Marliyati, Sri Anna; Damayanthi, Evy (Jurnal Gizi dan Pangan, 2016)
This study aimed to assess the effect of polyphenols in turkey berry fruits on level of antioxidant enzyme (erythrocyte superoxide dismutation [SOD]) and oxidative stress marker (serum 8-isoprostane) in obese adult women. The study was quasi experimental trial with cross-over design. Eight obese women subjects in Benteng Village-Ciampea, Bogor District, West Java were randomly assigned to a control group (n=4), and a turkey berry group (n=4) for 2 x 1 week daily treatment with a one week wash-out period between treatment periods. Turkey berry group consumed home diet and ±160 g of cooked turkey berry (as a side dish or snack) while the control group consumed only home diet. A food record consumption data was collected twice each week. Blood samples were obtained in the morning at day 1, 8, 15, and 22 of interventions and analyzed for the level of erythrocyte SOD and serum 8-isoprostane. The results showed that the different levels of erythrocyte SOD between post and pre intervention on turkey berry groups was not significantly different compared to the control group (p=0.607). Whereas, the different level of serum 8-isoprostane between post and pre intervention on turkey berry group in which decreasing was significantly different from the level on control group which was increasing (p<0.05). It seems that daily consumption of cooked turkey berry fruits can improve oxidative stress condition.